2012
DOI: 10.1029/2012jc007970
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale eddies in the northeastern Pacific tropical‐subtropical transition zone: Statistical characterization from satellite altimetry

Abstract: [1] Mesoscale eddies in the northeastern Pacific tropical-subtropical transition zone (16 N-30 N; 130 W-102 W) are analyzed using nearly 18 years of satellite altimetry and an automated eddy-identification algorithm. Eddies that lasted more than 10 weeks are described based on the analysis of 465 anticyclonic and 529 cyclonic eddy trajectories. We found three near-coastal eddy-prolific areas: (1) Punta Eugenia, (2) Cabo San Lucas, and (3) Cabo Corrientes. These three areas are located in places where the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 48 publications
(84 reference statements)
9
85
0
3
Order By: Relevance
“…These long-lived trajectories represent between 35% and 50% of the number of tracks formed near the coast, the rest are short-lived eddies. Note that it does not exist an official definition for ''long-lived eddies'' and, depending on the authors, the choice of their minimal duration can vary from a few weeks to several months [e.g., Fang and Morrow, 2003;Chaigneau and Pizarro, 2005;Chaigneau et al, 2008;Sangr a et al, 2009;Kurczyn et al, 2012;Chelton et al, 2007Chelton et al, , 2011Chaigneau et al, 2009;Chen et al, 2011]. Here we refer to ''long-lived eddies'' as eddies having a lifetime longer than 30 days, that is consistent with previous studies Figure 2.…”
Section: 1002/2015jc010950supporting
confidence: 77%
“…These long-lived trajectories represent between 35% and 50% of the number of tracks formed near the coast, the rest are short-lived eddies. Note that it does not exist an official definition for ''long-lived eddies'' and, depending on the authors, the choice of their minimal duration can vary from a few weeks to several months [e.g., Fang and Morrow, 2003;Chaigneau and Pizarro, 2005;Chaigneau et al, 2008;Sangr a et al, 2009;Kurczyn et al, 2012;Chelton et al, 2007Chelton et al, , 2011Chaigneau et al, 2009;Chen et al, 2011]. Here we refer to ''long-lived eddies'' as eddies having a lifetime longer than 30 days, that is consistent with previous studies Figure 2.…”
Section: 1002/2015jc010950supporting
confidence: 77%
“…For the TANWA these hot spots are associated with the headlands of Cap-Vert (Senegal) and Cap Timris (Mauretania). We could also confirm the existence of a seasonality in the eddy generation (Chaigneau et al, 2009;Kurczyn et al, 2012) and found cyclones form preferably during April to June, while anticyclones and ACMEs are mostly generated from October to December. After their generation, eddies of all three types propagate westward with a speed, c, of about 3.00 ± 2.15 km d −1 , which is in general agreement with the first baroclinic mode Rossby wave phase speed at that latitude range (Chelton et al, 1998).…”
Section: Discussionsupporting
confidence: 64%
“…The highest coastal upwelling rate in the CCS occurs in spring (Kurczyn et al 2012). This upwelling, combined with an especially strong equatorward flowing California Current, can explain the observed lowest …”
Section: ) Surroundings Of the Tropical Pacific Off Central Mexicomentioning
confidence: 99%
“…The poleward flow of the MCC corresponds to the cyclonic phase of this annual Rossby wave, but there are no studies to date that have described its complete seasonal and interannual variation. In the mesoscale, the dynamics of the TPCM are dominated by intense eddy activity (Kurczyn et al 2012(Kurczyn et al , 2013Lavín et al 2013). This current pattern, including the continuous exchanges through the entrance of the Gulf of California (Collins et al 2015), govern the spatial distribution and temporal variability of the water masses in the TPCM.…”
Section: Introductionmentioning
confidence: 99%